2016
DOI: 10.3390/md14050089
|View full text |Cite
|
Sign up to set email alerts
|

Dimethylsulfoniopropionate Promotes Process Outgrowth in Neural Cells and Exerts Protective Effects against Tropodithietic Acid

Abstract: The marine environment harbors a plethora of bioactive substances, including drug candidates of potential value in the field of neuroscience. The present study was undertaken to investigate the effects of dimethylsulfoniopropionate (DMSP), produced by several algae, corals and higher plants, on cells of the mammalian nervous system, i.e., neuronal N2a and OLN-93 cells as model system for nerve cells and glia, respectively. Additionally, the protective capabilities of DMSP were assessed in cells treated with tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Dimethylsulfoniopropionate (DMSP) promoted neurite outgrowth and protected against TDA-induced cytotoxicity, involving the upregulation of Hsp32 and activation of the extracellular signal-regulated kinases 1/2 (ERK1/2) [ 149 ]. Fucoxanthin has shown to exhibit neurite outgrowth activity (15.7–31% of cells to develop neurite outgrowth) at much lower concentrations (0.1–2 μM), in the absence of NGF support, indicating that this marine carotenoid could a potential neurotrophic molecule [ 136 ].…”
Section: Neuropharmacological Potentials Of Marine Algae and Theirmentioning
confidence: 99%
See 1 more Smart Citation
“…Dimethylsulfoniopropionate (DMSP) promoted neurite outgrowth and protected against TDA-induced cytotoxicity, involving the upregulation of Hsp32 and activation of the extracellular signal-regulated kinases 1/2 (ERK1/2) [ 149 ]. Fucoxanthin has shown to exhibit neurite outgrowth activity (15.7–31% of cells to develop neurite outgrowth) at much lower concentrations (0.1–2 μM), in the absence of NGF support, indicating that this marine carotenoid could a potential neurotrophic molecule [ 136 ].…”
Section: Neuropharmacological Potentials Of Marine Algae and Theirmentioning
confidence: 99%
“…Potentials of tramiprosate against AD and PD have also been reviewed elsewhere [ 28 , 209 , 210 ]. Dimethylsulfoniopropionate protected against tropodithietic acid-induced cytotoxicity in OLN-93 and N2a cells by lowering the activation of ERK1/2 and induction of HSP32 [ 149 ]. Phycoerythrin-derived peptide isolated from Pyropia yezoensis promoted survivability of frontal cortical neuron by activating TrkB receptor-ERK1/2 signaling and attenuating ER stress in rat prefrontal cortex [ 211 ] and attenuated glutamate-induced ER stress and senescence of rat primary hippocampal neurons [ 212 ].…”
Section: Neuropharmacological Potentials Of Marine Algae and Theirmentioning
confidence: 99%
“…Recent studies remarkably showed that the cytotoxic effects of 15 against eukaryotic cells are dampened by 22 (produced, e. g., by corals and algae), suggesting that it may not only serve as food for bacteria but also to protect the hosts themselves from their 15-synthesizing microbial symbionts (see also Section 5.1.2.). [106] In the following sections, we will highlight studies that imply a potential role of 15 in mutualistic symbiotic relationships.…”
Section: Tropodithietic Acid Producers Host Organisms and Symbioticmentioning
confidence: 99%
“…[141] A later study by the same group remarkably showed that 22 is likely anti-oxidative and protects cells to some extent against the toxic effects of 15. [106] As dimethyl sulfone (that is structurally similar to 22) can cross the blood-brain barrier and because up to 5 mg/mL of 22 showed no cytotoxicity against eukaryotic cells but rather acted neuroprotective in rodents, [142] it may be worthwhile to further study the effects of 22 in combination with 15. It would be interesting to see if, for example, if 15 still maintains anti-cancer and/or antimicrobial activity in presence of 22 (also from an ecological perspective regarding symbiotic relationships of 15-producing bacteria with 22-generating marine invertebrates and algae, see 4.2).…”
Section: Toxicity Of Tropodithietic Acid and Protective Effects Of Dmspmentioning
confidence: 99%
“…The switch between mutualism and parasitism in algaebacteria interactions has also been found in the interaction between the dinoflagellate Prorocentrum minimum and Dinoroseobacter shibae 2015a,b). It was suggested that D. shibae obtains its energy by degradation of polyhydroxyalkanoate and dimethylsulfoniopropionate (DMSP) , pathways that are also present in P. inhibens (Dickschat et al, 2010;Kanehisa et al, 2016) and with the latter molecule actually preventing the effect of TDA (Wichmann et al, 2016). Additionally, E. huxleyi is a known producer of DMSP (Wolfe and Steinke, 1996;Steinke et al, 2007).…”
Section: Bacterial-microalgal Co-cultivationmentioning
confidence: 99%